2018
DOI: 10.1186/s12888-018-1972-8
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities are different in Schizophrenic Spectrum Disorders, Bipolar Disorder and Major Depressive Disorder

Abstract: BackgroundResearch has shown that a history of childhood adversities is common in patients with psychiatric disorders but few studies have investigated links between specific types of adversity and specific psychiatric disorders.MethodsWe investigated the frequency of early childhood adversities in a sample consisting of 91 patients with diagnosis of schizophrenic spectrum disorders (SSD), 74 patients with bipolar disorder (BD), 83 patients with major depressive disorder (MDD) and 85 healthy controls and sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…Some changes occur in the families of people living with bipolar disorder that cause other family members to be unable to reach their maximum potential in different areas. Stigma experienced in these families can have adverse consequences, such as feelings of shame and frustration, distance from others, and being exposed to injustice and discrimination [21,22]. Numerous studies have shown that 40% of families hide their patients' hospitalization from others, and the fear of being stigmatised is considered the most critical and significant obstacle for patients and their families to benefit from medical services and social support [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Some changes occur in the families of people living with bipolar disorder that cause other family members to be unable to reach their maximum potential in different areas. Stigma experienced in these families can have adverse consequences, such as feelings of shame and frustration, distance from others, and being exposed to injustice and discrimination [21,22]. Numerous studies have shown that 40% of families hide their patients' hospitalization from others, and the fear of being stigmatised is considered the most critical and significant obstacle for patients and their families to benefit from medical services and social support [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the CTQ total score is also associated with higher PTH levels. Childhood traumas increase the lifetime risk to develop BD [ 47 ] and are associated with a greater clinical severity [ 48 ] and a more severe clinical course (i.e., rapid cycling, early age of onset, suicide attempts and more depressive episodes) [ 49 ]. In BD patients, a history of childhood trauma leads to difficulties in affective regulation, impulse control, cognitive functioning and neurobiological modifications due to the epigenetic consequences of early trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in neuroscience [29], found that patients with schizophrenia had higher scores for emotional neglect and physical neglect, and lower utilization scores for physical abuse and subjective support. Bruni [30] refined the types of childhood trauma, and proposed that among the types of childhood trauma suffered by schizophrenia patients, cannabis abuse, loneliness, running away from home, mental abuse, physical abuse and schizophrenia are more related.…”
Section: Childhood Traumamentioning
confidence: 99%